Answer:
<h2>
10. C. (2, -1)</h2><h2>
11. B. (-2, -4)</h2>
Step-by-step explanation:
10.
![\left \{ {{x-2y=4} \atop {4x+2y+6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-2y%3D4%7D%20%5Catop%20%7B4x%2B2y%2B6%7D%7D%20%5Cright.)
The y values cancel out if you add the equations
5x = 10
x = 2
plug in x
2 - 2y = 4
-2y = 2
y=-1
Answer: C. (2, -1)
11.
![\left \{ {{6x-2y=-4} \atop {-4x+3y=-4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B6x-2y%3D-4%7D%20%5Catop%20%7B-4x%2B3y%3D-4%7D%7D%20%5Cright.)
In order to get terms to cancel out, multiply the top by 3 and bottom by 2
![\left \{ {{18x-6y=-12} \atop {-8x+6y=-8}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B18x-6y%3D-12%7D%20%5Catop%20%7B-8x%2B6y%3D-8%7D%7D%20%5Cright.)
The y values cancel out if you add the equations
10x = -20
x = -2
plug in x
6(-2) - 2y = -4
-12 - 2y = -4
-2y = 8
y = -4
Answer: B. (-2, -4)
Answer:
4n^2 + 22n
Step-by-step explanation:
10(n^2+n) -6 (n^2 - 2)
10n^2 + 10n - 6n^2 + 12
4n^2 + 22n
I believe the correct answer from the choices listed above is the last option. THe missing step of her solution would be the statement "<span>Divide both sides of the equation by 10.4." Hope this answers the question. Have a nice day.</span>
Answer:
the answer is equal because 8/12=2/3 so 2/3=8/12 (2/3)
Step-by-step explanation: